Visualisasi Dashboard Business Intelligence Untuk Analisa Ketersediaan Tenaga Kesehatan Pada Saat Covid-19 Di Jakarta Menggunakan Tableau - Panji Islami Anakku; E Erizal; Firman Noor Hasan (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2023)
The Covid-19 pandemic in 2020 witnessed a significant increase in cases worldwide, claiming numerous lives. Despite having a substantial number of healthcare workers in several hospitals in DKI Jakarta, there remained a shortage of healthcare personnel during the Covid-19 outbreak. Consequently, there were still many deaths attributed to both diseases. This study aims to analyze self-data visualization from opendatajakarta in the form of a dashboard and utilize the storytelling feature available in Tableau for visualization. The research aims to determine the number of healthcare workers during the major Covid-19 outbreak in DKI Jakarta. To achieve this, the study employs a method called Business Intelligence using the interactive dashboard options provided by Tableau as a decision-making tool, which will be transformed into visualizations and combined into an information dashboard. The research obtained results in the form of a Business Intelligence dashboard displaying the number of healthcare workers in DKI Jakarta.